Anti-inflammatory effects of excessive weight loss: potent suppression of adipose interleukin 6 and tumour necrosis factor α expression. Issue 9 (21st July 2010) - Moschen, Alexander R; Molnar, Clemens; Geiger, Sabine; Graziadei, Ivo; Ebenbichler, Christoph F; Weiss, Helmut; Kaser, Susanne; Kaser, Arthur; Tilg, Herbert
Abstract : Objective: Severe obesity is a chronic inflammatory disease where various cytokines/adipocytokines play a key role. Pro-inflammatory cytokines such as interleukin 6 (IL-6) and tumour necrosis factor-α (TNFα) are produced by human adipose tissue dependent on the degree of obesity. Mouse studies suggest a key role of adipose tissue-derived IL-6 in hepatic insulin resistance via modification of liver suppressor of cytokine signalling 3 (SOCS-3) expression. Design and methods: We examined the effect of excessive weight loss on systemic levels, subcutaneous and visceral adipose tissue and liver expression of IL-6 and TNFα in 20 severely obese patients undergoing laparoscopic adjustable gastric banding (LAGB). Furthermore, we studied liver expression of SOCS3, an important regulator of insulin resistance, and fat tissue expression of the anti-inflammatory adipocytokine adiponectin and its receptors. Serum and tissue samples were collected before and 6 months after LAGB surgery. Results: IL-6/TNFα mRNA expression before weight loss were similar in subcutaneous and visceral adipose tissue and much higher compared to hepatic expression. Subcutaneous adipose tissue mRNA expression of both pro-inflammatory cytokines, but especially of IL-6 decreased dramatically after extensive weight loss whereas expression of adiponectin and its receptors increased. Weight loss also led to a significant reduction in liver IL-6 expression, whereas liver TNFα mRNA expression did not change. IL-6 and C-reactive protein serum levels decreased after weight loss whereas TNFα serum levels were below the detection limit before and after surgery. These effects were paralleled by reduced hepatic SOCS3 expression and improved insulin resistance 6 months after LAGB surgery. Conclusion: Expression of IL-6 and TNFα mRNA is more pronounced in adipose compared to liver tissue in patients with severe obesity. Our results highlight excessive weight loss as a successful anti-inflammatory strategy.